EVALUASI BELAJAR PENDIDIKAN DASAR 9 TAHUN MELALUI MADRASAH DI KABUPATEN PANDEGLANG - K. SUKARDJI (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2001)
In the Framework to raise the progress of the nation life entirely, the goverment has carried out the nine years - Basic Education Compulsory Programme (Wajar Dikdas) through general school and Islamic school In this programme through the Islamic school among others have been done in model school of Islamic elementery school (MIN) in village of part, Mandalawangi, Pandeglang and the Islamic secondary private scool